2016
DOI: 10.1128/genomea.01041-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus cereus LCR12, a Plant Growth–Promoting Rhizobacterium Isolated from a Heavy Metal–Contaminated Environment

Abstract: Bacillus cereus LCR12 is a plant growth–promoting rhizobacterium, isolated from a heavy metal–contaminated environment. The 6.01-Mb annotated genome sequence provides the genetic basis for revealing its potential application to remediate contaminated soils in association with plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the current study, we isolated and investigated the effect of B. cereus as a heavy metal remediator to alleviate the toxic effects of Cd +2 on rice biomass, cell membrane stability, metabolites, and antioxidants. Previously it was reported by Egidi et al [42] that B. cereus can be used as a toxic metals remediator. Similarly, it was observed that inoculation of plant growth promoting bacteria (PGPB) are supposed to be highly efficient remediation method mainly for salinity [43] and heavy metals [44] without any harmful effects on soil and plant.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we isolated and investigated the effect of B. cereus as a heavy metal remediator to alleviate the toxic effects of Cd +2 on rice biomass, cell membrane stability, metabolites, and antioxidants. Previously it was reported by Egidi et al [42] that B. cereus can be used as a toxic metals remediator. Similarly, it was observed that inoculation of plant growth promoting bacteria (PGPB) are supposed to be highly efficient remediation method mainly for salinity [43] and heavy metals [44] without any harmful effects on soil and plant.…”
Section: Discussionmentioning
confidence: 99%
“…B. cereus is a Gram-positive, spore-forming, rod-like bacterium belonging to the Bacillus genus. The whole-genome sequencing of B. cereus isolated from the rhizosphere and endosphere of plants has revealed notable genes in their genome, more importantly, plant growth-promoting genes [ 21 , 22 ]. In addition, Hong et al [ 23 ] have reported the complete genome sequence of endophytic bacterium B. cereus strain PgBE311 isolated from Panax ginseng .…”
Section: Introductionmentioning
confidence: 99%
“…The (30) Actinobacteria (2) This study Disease/pathogen/insect control Bacillus pumilus [30,43] two bacilli have been reported as PGPB. In the case of B. cereus LCR12 [46], both growth promotion and heavy metal detoxification activities were found. B. pumilus is a well-established biological control agent for crops; B. pumilus increases defense against blue mold in tobacco [43] and suppresses gray leaf spot disease in pepper [30].…”
Section: Alkali-tolerant Bacteria Of Dokdo As Pgpbmentioning
confidence: 99%